Confined iron-based nanomaterials for water decontamination: Fundamentals, applications, and challenges - Wanyi Fu; Ziyao Liu; Zhichao Yang; Yuhang Li; Bingcai Pan (Fundamental Research)
Nanotechnology-enabled water treatment is the most attractive approach to realizing advanced purification of contaminated waters that challenge the efficacy of traditional water treatment technologies. Confining nanomaterials inside porous scaffolds or substrates is one of the most effective strategies to push nano-enabled water treatment technologies forward from laboratory to field application. As flourishingly reported, confinement effects induce significantly improved decontamination efficiency, such as enhanced adsorption capacity, reaction kinetics, stability, and selectivity. In this review, first we provide an overview of the general fundamentals of nanoconfinement effects and their implications in environmental remediation. Next, we review confined Fe-based nanomaterials, such as different polymorphs of iron-oxides, oxyhydroxides, zero-valent iron, and single-atom iron as representative materials towards their applications in nanoconfinement systems for water decontamination. Finally, we propose future studies based on the missing scientific fundamentals regarding nanoconfinement effects and challenges for translating unique and promising nanoconfinement observations to engineering applications of confined nanomaterials-driven water treatment technologies.